Réseau de la finance solidaire et responsable au QuébecCo-construction d’un champ institutionnel dans l’écosystème d’économie sociale et solidaire - Tassadit Zerdani; Marie J. Bouchard (Revue Interventions Économiques)
This article shows the role of actors and their groups in the emergence and development of a social economy ecosystem through the analysis of the Quebec solidarity and responsible finance sector case and of the network formed by these actors. Based on data from a longitudinal study, the article describes the main actors in this sector and analyzes the institutionalization process of their network. This case illustrates how the networking practices and actions allow co-constructing and developing of a new institutional field, which is different from the traditional financial field. It shows that, by the formalization of their network, the solidarity and responsible finance actor’s aim, not only the development and sustainability of their own organizations, but also that of the Québec social economy ecosystem, especially by influencing public policies.